A proposal for telemedicine reference model for future standardization - Komiya, , R (2005)
This paper describes a telemedicine reference model for future standardization [1]. The necessity of the telemedicine reference model has been recognized by ITU-T/D to realize telemedicine equipment portability internationally [2]. Specifically, just in the case of Tsunami disasters on 26 December 2004, wide regional areas in Indian Sea were attacked and more than 273,000 people died [3]. In such a disaster, international medical team co-operations should be necessary, and actually many medical teams came to rescue the wounded.